Synthesis and SAR of the antistaphylococcal natural product nematophin from Xenorhabdus nematophila - Wesche, Frank; Adihou, Hélène; Wichelhaus, Thomas A.; Bode, Helge B. (Beilstein Journal of Organic Chemistry, 2019)
The repeated and improper use of antibiotics had led to an increased number of multiresistant bacteria. Therefore, new lead structures are needed. Here, the synthesis and an expanded structure–activity relationship of the simple and antistaphylococcal amide nematophin from Xenorhabdus nematophila and synthetic derivatives are described. Moreover, the synthesis of intrinsic fluorescent derivatives, incorporating azaindole moieties was achieved for the first time.
Keywords: azaindole; fluorescent dye; MRSA; nematophin; Staphylococcus aureus